Multiple Coronary Fistulas as a Rare Cause of Stable Angina Pectoris - Jasna Čerkez Habek; Tea Friščić; Jozica Šikić; Marko Perčić; Dean Strinić; Daria Ljubas Perčić (Case Reports in Cardiology)
Congenital coronary artery-left ventricular multiple microfistulas (CA-LVMMFs) are rare anomalies in adults. They are more often found in female patients, and they usually originate from the distal segments of the coronary arteries, but they can originate from a proximal segments of a coronary arteries, and these patients are likely to be identified and treated in the pediatric age group. They are mostly asymptomatic. When symptoms and complications occur, they include angina, myocardial infarction, atrial heart failure, arrhythmias, and endocarditis. The management of CA-LVMMFs is controversial, but it is generally agreed that conservative medical management is the primary treatment of choice. Our case describes a rare form of CA-LVMMFs draining into the left ventricle in a female patient presenting with fatigue, atypical anginal symptoms, atrial fibrillation, and premature ventricular complexes, without concomitant obstructive coronary artery disease.